To aggregate or not to aggregate? Euro area inflation forecasting - Nicholai Benalal; Juan Luis Diaz del Hoyo; Bettina Landau; Moreno Roma; Frauke Skudelny (European Central Bank (ECB), 2004)
In this paper we investigate whether the forecast of the HICP components (indirect approach) improves upon the forecast of overall HICP (direct approach) and whether the aggregation of country forecasts improves upon the forecast of the euro-area as a whole, considering the four largest euro area countries. The direct approach provides clearly better results than the indirect approach for 12 and 18 steps ahead for the overall HICP, while for shorter horizons the results are mixed. For the euro area HICP excluding unprocessed food and energy(HICPX), the indirect forecast outperforms the direct whereas the differences are only marginal for the countries. The aggregation of country forecasts does not seem to improve upon the forecast of the euro area HICP and HICPX. This result has however to be taken with caution as differences appear to be rather small and due to the limited country coverage.
Keywords: C11; C32; C53; E31; E37; 330; Bayesian VARs; Forecasting short-term inflation; HICP sub-components/aggregation; Model Selection